2015
DOI: 10.1364/oe.23.00a204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hybrid white light-emitting diodes by organic-inorganic materials at different CCT from 3000K to 9000K

Abstract: The hybrid white light-emitting didoes (LED) with polyfluoren (PFO) polymer and quantum dot (QD) was investigated using dispensing method at the different correlated color temperature (CCT) for cool and warm color temperature. This result indicates that the hybrid white LED device has the higher luminous efficiency than the convention one, which could be attributed to the increased utilization rate of the UV light. Furthermore, the CIE 1931 coordinate of high quality white hybrid LED with different CCT range f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In general, LEDs were recognized as one kind of the economical and efficient solid-state lighting sources [1,2]. In order to achieve high color rendition (Ra > 80) of white LEDs, the component ratio of green light and red light should be larger.…”
Section: Introductionmentioning
confidence: 99%
“…In general, LEDs were recognized as one kind of the economical and efficient solid-state lighting sources [1,2]. In order to achieve high color rendition (Ra > 80) of white LEDs, the component ratio of green light and red light should be larger.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the inorganic nanocrystal, or quantum dots, they are both competitive for the future generation of light sources because of their good quantum yields. In our previous work, the blue polyfluorene seems to be promising in terms of good quantum yield demonstrated [28].…”
Section: Introductionmentioning
confidence: 96%
“…The results from their study showed that CaF2-YAG:Ce phosphor ceramic increase the optical performance of WLEDs, specifically, the increased luminous flux, CCT and CRI are 359.7 lm, 4021-7941 K and 70.1-82.7, respectively. The potential to boost the effectiveness of these nanoparticles is high as they are compact and flexible which open directions for alterations yet there are not many manuscripts on utilizing nanoparticles in a creative structure as most research concentrate on how WLEDs react to the particles [22][23][24]. In the meantime, because of the lack of concentrated speculations and complex specialized direction, choosing an optimal nanoparticles material to effectively enhance the CCT is quite confusing and repetitive, especially for manufacturers.…”
Section: Introductionmentioning
confidence: 99%